MANAJEMEN KURIKULUM INTEGRATIF DALAM MENINGKATKAN KARAKTER RELIGIUS DI PESANTREN TAHFIDZ AL IKHLAS DUKUH BIMA BEKASI - Setiawan, Hendra; Yaskur, Muhammad; Al Mufti, Muflihin (UNISAN JURNAL, 2025)
The objectives of this study are: first, to describe the integrative pesantren-madrasah curriculum model in enhancing the religious character of students at Ma’had Tahfidz Al Ikhlas Dukuh Bima Bekasi. Second, to describe the planning of the integrative pesantren-madrasah curriculum in enhancing the students’ religious character at the same institution. Third, to describe the implementation of the integrative pesantren-madrasah curriculum. Fourth, to describe the evaluation of the integrative pesantren-madrasah curriculum in fostering students’ religious character. This study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The data were analyzed through data reduction, data display, and data verification. The results show that the managerial system is not centralized in the hands of the principal alone but is supported by a team assigned as the management group. In detail, the research findings are: (1) The integrative curriculum management (pesantren-madrasah) in enhancing religious character is based on an integration model within a single discipline, meaning a curriculum organization model that merges competencies of different subjects within one unified subject. (2) The planning of the integrative curriculum involves: a) integrating curriculum objectives—aligning the vision of general and religious knowledge development, followed by preparing annual programs, semester programs, and lesson plans (RPP); and b) integrating curriculum content by combining the Islamic studies (Ta’lim Dirasah Islamiyah) from the pesantren with the Islamic Education subjects in the madrasah. (3) The implementation of the integrative curriculum is carried out by competent teachers, excellent students, and the madrasah head through: a) integrating curriculum implementation programs—unifying the academic calendar and activity plans of the pesantren and madrasah; and b) integrating curriculum supervision through collaboration between the pesantren leader and madrasah head. (4) The evaluation of the integrative curriculum is conducted in a coordinated manner between the madrasah and pesantren, covering: a) context evaluation, b) input evaluation, c) process evaluation, and d) product evaluation of the curriculum.